Addition-curable liquid silicone rubber composition and electrophotographic image forming member
Patent Information
- Application Number
- JP2021206736
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-12-21
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2041-12-21
AI Technical Summary
【0011】 本発明によれば、良好な保存安定性、特に経時の硬化性安定性を有する硬化物を与える付加硬化型液状シリコーンゴム組成物を提供することができ、特に電子写真式画像形成部材用の付加硬化型液状シリコーンゴム組成物及び該組成物の硬化物を弾性層として有する電子写真式画像形成部材が得られる。
Smart Images

Figure 0007630892000001 
Figure 0007630892000002 
Figure 0007630892000003
Abstract
Description
[Technical field]
[0001] The present invention relates to an addition-curable liquid silicone rubber composition and an electrophotographic imaging member. [Background technology]
[0002] Taking advantage of its heat resistance, silicone rubber has been used as a coating material for the fuser rolls of copiers and laser beam printers, which require high thermal conductivity, in particular a thermal conductivity higher than that of silicone oil, 0.16 W / m K.
[0003] In response to such demands, a method has been proposed in which metal silicon powder is used to improve thermal conductivity and also dramatically improve compression set (Patent Document 1).
[0004] In addition, a technique has been proposed in which a native oxide film with few defects is formed on metallic silicon powder by heat treatment and wet treatment, and then the surface is further treated with an organosilicon compound such as a silane coupling agent (Patent Document 2). [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2007-171946 A [Patent Document 2] JP 2013-216576 A Summary of the Invention [Problem to be solved by the invention]
[0006] However, when metallic silicon powder is added to addition-curing liquid silicone rubber, the metallic silicon powder adversely affects the addition-curing catalyst. This problem of delayed curing over time has not been resolved, and there has been a demand for the development of a silicone rubber composition that has high thermal conductivity and excellent storage stability.
[0007] The object of the present invention is to provide an addition-curing liquid silicone rubber composition having improved storage stability, in particular in which delay in curing over time, is suppressed, and to provide an electrophotographic image-forming member having an elastic layer made of the cured product of the composition, in the form of a highly thermally conductive addition-curing liquid silicone rubber composition containing a thermally conductive powder. [Means for solving the problem]
[0008] As a result of intensive research by the inventors in order to achieve the above-mentioned object, they have discovered that, in an addition-curing liquid silicone rubber composition containing the components (A) to (E) described below, a thermally conductive silicone rubber composition blended with an addition reaction catalyst, component (C), a thermally conductive powder, component (D), and an alkenyl-containing organopolysiloxane having a specific structure, component (E), is able to inhibit delay in curing over time and has good storage stability. They also discovered that a thermally conductive silicone rubber member (roll, belt, etc.) having a silicone rubber layer formed by curing this composition has excellent thermal conductivity and can be effectively used as a rubber member for high-speed copiers and printers, which has led to the completion of the present invention.
[0009] Accordingly, the present invention provides an addition-curable liquid silicone rubber composition and an electrophotographic imaging member as described below. [1] (A) A compound having two or more alkenyl groups bonded to silicon atoms in one molecule, and the content of the alkenyl groups bonded to silicon atoms is 1.0 × 10 relative to the total number of monovalent hydrocarbon groups bonded to silicon atoms. -7 ~1.0×10 -3 mol / g liquid organopolysiloxane: 100 parts by mass, (B) an organohydrogenpolysiloxane containing two or more hydrosilyl groups per molecule: the number of hydrosilyl groups contained in component (B) is 0.4 to 10 per alkenyl group bonded to a silicon atom contained in component (A); (C) a platinum group metal catalyst as an addition reaction catalyst: an amount equivalent to 0.5 to 1,000 ppm, calculated as a platinum group metal, based on the total mass of the component (A); (D) a thermally conductive powder having an average primary particle size of 75 μm or less and a thermal conductivity of 10 W / m K or more: 10 to 1,000 parts by mass, and (E) An alkenyl-containing cyclic organopolysiloxane in which all silicon atoms have one or more alkenyl groups, and the content of alkenyl groups bonded to silicon atoms is 1.1×10 relative to the total number of monovalent hydrocarbon groups bonded to silicon atoms. -3 ~1.0×10 -1 mol / g of alkenyl-containing linear organopolysiloxanes in an amount of 0.1 to 500 mol per 1 mol of platinum group metal atoms in component (C). [2] The addition-curable liquid silicone rubber composition according to [1], wherein component (D) is metallic silicon powder. [3] The addition-curing liquid silicone rubber composition according to [1], wherein component (D) is a metallic silicon powder or a thermally conductive powder having a Mohs hardness higher than that of the metallic silicon powder. [4] The alkenyl group-containing cyclic organopolysiloxane in component (E) is represented by the following general formula (1): [ka] (In the formula, R 1 is a methyl group or a vinyl group, and p is 3 to 30. The alkenyl group-containing linear organopolysiloxane in component (E) is represented by the following general formula (2): [ka] (In the formula, R is independently a monovalent hydrocarbon group having 1 to 10 carbon atoms, q is 0 or more, r is 2 or more, and q+r is 2 to 200.) The addition-curable liquid silicone rubber composition according to any one of [1] to [3], wherein the composition is represented by the formula: [5] An electrophotographic image forming member having an elastic layer made of a cured product of the addition-curable liquid silicone rubber composition according to any one of [1] to [4]. [6] The electrophotographic image forming member according to [5], wherein the electrophotographic image forming member is a member selected from a fixing roll and a fixing belt.
[0010] When the addition-curable liquid silicone rubber composition is as described above in [1], it is possible to obtain a cured product that has good storage stability and suppresses delay in curing over time. By using the organopolysiloxane of the above formula (4), it is possible to maintain the storage stability of the addition reaction catalyst of the component (C). The addition-curable liquid silicone rubber composition of the present invention can be particularly suitably used in applications such as the above items [5] and [6]. Effect of the Invention
[0011] According to the present invention, it is possible to provide an addition-curable liquid silicone rubber composition that gives a cured product having good storage stability, in particular curing stability over time, and in particular to obtain an addition-curable liquid silicone rubber composition for electrophotographic image-forming members and an electrophotographic image-forming member having a cured product of said composition as an elastic layer. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] The present invention will be described in detail below.
[0013] <Addition-curable liquid silicone rubber composition> The addition-curable liquid silicone rubber composition (addition-curable highly thermally conductive silicone rubber composition) of the present invention comprises the following components (A) to (E).
[0014] [Component (A)] Component (A) is a liquid (particularly liquid at 25°C) organopolysiloxane containing two or more alkenyl groups bonded to silicon atoms in each molecule, and is the base polymer (main component) of the composition of the present invention.
[0015] The molecular structure of component (A) may be, for example, linear, cyclic, branched, or three-dimensional network (resinous), but is preferably a linear diorganopolysiloxane whose main chain is basically composed of repeated diorganosiloxane units and whose molecular chain ends are blocked with triorganosiloxy groups. When the molecular structure of the organopolysiloxane of component (A) is linear or branched, the position of the silicon atom to which the alkenyl group is bonded in the organopolysiloxane molecule may be either or both of the molecular chain end (i.e., triorganosiloxy group) and the middle of the molecular chain (i.e., difunctional diorganosiloxane unit or trifunctional monoorganosilsesquioxane unit located at non-terminal of the molecular chain). Particularly preferred as component (A) is a linear diorganopolysiloxane containing alkenyl groups bonded to silicon atoms at both molecular chain ends.
[0016] The alkenyl group bonded to the silicon atom in component (A) typically has from 2 to 8 carbon atoms, and preferably has from 2 to 4 carbon atoms. Specific examples include vinyl groups, allyl groups, butenyl groups, pentenyl groups, hexenyl groups, cyclohexenyl groups, and heptenyl groups, with vinyl groups being particularly preferred.
[0017] The content of alkenyl groups bonded to silicon atoms in component (A) is 1.0 x 10 relative to the total number of monovalent hydrocarbon groups bonded to silicon atoms. -7 ~1.0×10 -3 mol / g, 1.0×10 -6 ~5.0×10 -4 It is preferably expressed in mol / g.
[0018] Examples of monovalent hydrocarbon groups bonded to silicon atoms other than alkenyl groups in component (A) include monovalent hydrocarbon groups having 1 to 12 carbon atoms, and preferably 1 to 10 carbon atoms. Specific examples of monovalent hydrocarbon groups include alkyl groups such as methyl, ethyl, propyl, butyl, pentyl, hexyl, cyclohexyl, and heptyl; aryl groups such as phenyl, tolyl, xylyl, and naphthyl; and aralkyl groups such as benzyl and phenethyl. Of these, methyl groups are particularly preferred.
[0019] The viscosity of component (A) at 25°C is preferably 50 to 500,000 mPa·s, and more preferably 500 to 200,000 mPa·s. If the viscosity is within this range, the resulting silicone rubber composition is easy to handle and the cured product of the resulting silicone rubber composition has good mechanical properties. In this specification, the viscosity refers to the value measured at 25°C using a rotational viscometer according to the method described in JIS K 7117-1:1999.
[0020] Specific examples of organopolysiloxanes of component (A) include dimethylsiloxane-methylvinylsiloxane copolymers capped at both molecular chain terminals with trimethylsiloxy groups, methylvinylpolysiloxanes capped at both molecular chain terminals with trimethylsiloxy groups, dimethylsiloxane-methylvinylsiloxane-methylphenylsiloxane copolymers capped at both molecular chain terminals with trimethylsiloxy groups, dimethylpolysiloxanes capped at both molecular chain terminals with dimethylvinylsiloxy groups, methylvinylpolysiloxanes capped at both molecular chain terminals with dimethylvinylsiloxy groups, and dimethylsiloxane-methylvinylpolysiloxanes capped at both molecular chain terminals with dimethylvinylsiloxy groups. and mixtures of two or more of these organopolysiloxanes.
[0021] The organopolysiloxane of component (A) may be used alone or in combination of two or more kinds, of which the use of two or more kinds in combination is preferred because it makes it easier to adjust the viscosity of the composition of the present invention to a preferred range.
[0022] [(B) Component] The organohydrogenpolysiloxane of component (B) undergoes a hydrosilylation addition reaction with the alkenyl groups in component (A) and acts as a crosslinking agent (curing agent). There are no particular limitations on its molecular structure, and various types of conventionally produced structures can be used, such as those with linear, cyclic, branched, and three-dimensional network (resinous) structures, but it is necessary for each molecule to contain two or more hydrosilyl groups.
[0023] The organohydrogenpolysiloxane of the component (B) may use either a single compound, or a combination of two or more different compounds.
[0024] As this organohydrogenpolysiloxane, one represented by the following average composition formula (3) can be used. R 2 a H b SiO (4-a-b) / 2 (3) (In the formula, R 2 are independently a group selected from an alkyl group having 1 to 10 carbon atoms, an aryl group having 6 to 10 carbon atoms, and an aralkyl group having 7 to 10 carbon atoms. In addition, a is a positive number that satisfies 0.7 to 2.1, b is a positive number that is 0.001 to 1.0, and a+b is a positive number that satisfies 0.8 to 3.0.
[0025] In the above formula (3), R 2 are independently a group selected from an alkyl group having 1 to 10 carbon atoms, an aryl group having 6 to 10 carbon atoms, and an aralkyl group having 7 to 10 carbon atoms, 2 Examples of the monovalent hydrocarbon group in the above formula include alkyl groups such as methyl, ethyl, propyl, isopropyl, butyl, isobutyl, tert-butyl, pentyl, neopentyl, hexyl, cyclohexyl, octyl, nonyl, and decyl; aryl groups such as phenyl, tolyl, xylyl, and naphthyl; and aralkyl groups such as benzyl, phenylethyl, and phenylpropyl. 2 is preferably an alkyl group or an aryl group, and more preferably a methyl group. Furthermore, a is a positive number that satisfies 0.7 to 2.1, b is a positive number that satisfies 0.001 to 1.0, and a+b is a positive number that satisfies 0.8 to 3.0, and preferably a is a positive number that satisfies 1.0 to 2.0, b is a positive number that satisfies 0.01 to 1.0, and a+b is a positive number that satisfies 1.5 to 2.5.
[0026] The hydrosilyl group contained in one molecule may be located at either the molecular chain terminal or the molecular chain middle, or may be located at both. The molecular structure of this organohydrogenpolysiloxane may be any of linear, cyclic, branched, and three-dimensional network structures, but the number of silicon atoms (or degree of polymerization) in one molecule is usually 2 to 300, preferably 3 to 150, and more preferably 4 to 100, and the viscosity at 25°C is usually about 0.1 to 1,000 mPa·s, preferably about 0.5 to 500 mPa·s, and the one that is liquid at 25°C is used. In this specification, the degree of polymerization can be determined, for example, as the number average degree of polymerization (number average molecular weight) or weight average degree of polymerization (weight average molecular weight) in terms of polystyrene in GPC (gel permeation chromatography) analysis using toluene as a developing solvent.
[0027] Examples of organohydrogenpolysiloxanes of component (B) include 1,1,3,3-tetramethyldisiloxane, 1,3,5,7-tetramethylcyclotetrasiloxane, tris(hydrogendimethylsiloxy)methylsilane, tris(hydrogendimethylsiloxy)phenylsilane, methylhydrogencyclopolysiloxane, methylhydrogensiloxane-dimethylsiloxane cyclic copolymers, methylhydrogenpolysiloxanes capped with trimethylsiloxy groups at both molecular chain ends, dimethylsiloxane-methylhydrogensiloxane copolymers capped with trimethylsiloxy groups at both molecular chain ends, dimethylsiloxane-methylhydrogensiloxane-methylphenylsiloxane copolymers capped with trimethylsiloxy groups at both molecular chain ends, dimethylsiloxane-methylhydrogensiloxane-methylphenylsiloxane copolymers capped with trimethylsiloxy groups at both molecular chain ends, dimethylsiloxane-methylhydrogensiloxane-diphenylsiloxane copolymers capped with trimethylsiloxy groups at both molecular chain ends, and dimethylsiloxane-methylhydrogensiloxane-diphenylsiloxane and compounds having the formula: R 3 3SiO 1 / 2 Siloxane units represented by the formula: R 3 2HSiO 1 / 2 Siloxane units represented by the formula: SiO 4 / 2 Organosiloxane copolymers consisting of siloxane units represented by the formula: R 3 2HSiO 1 / 2 Siloxane units represented by the formula: SiO 4 / 2 Organosiloxane copolymers consisting of siloxane units represented by the formula: R3 HSiO 2 / 2 Siloxane units represented by the formula: R 3 SiO 3 / 2 Siloxane unit or formula: HSiO 3 / 2 and mixtures of two or more of these organopolysiloxanes. 3 is a group selected from an alkyl group having 1 to 10 carbon atoms, an aryl group having 6 to 10 carbon atoms, and an aralkyl group having 7 to 10 carbon atoms, and is particularly preferably a methyl group.
[0028] The amount of component (B) added is an amount such that there are 0.4 to 10 (or moles), preferably 0.5 to 5 (or moles), and more preferably 0.5 to 2.0 (or moles) hydrosilyl groups in component (B) per one (or mole) silicon-bonded alkenyl group in component (A).
[0029] If the number of hydrosilyl groups in component (B) is less than 0.4 per silicon-bonded alkenyl group in component (A), the silicone rubber composition will not cure sufficiently and may not achieve the desired strength, whereas if the number of hydrosilyl groups in component (B) is more than 10, the heat resistance of the cured product of the silicone rubber composition may be significantly reduced.
[0030] [(C) component] Examples of the addition reaction catalyst for component (C) include platinum group metal catalysts such as platinum black, platinic chloride, chloroplatinic acid, reaction products of chloroplatinic acid and monohydric alcohols, complexes of chloroplatinic acid and olefins, platinum bisacetoacetate, etc., palladium catalysts, and rhodium catalysts.
[0031] The amount of component (C) to be blended is the catalyst amount, i.e., an amount equivalent to 0.5 to 1,000 ppm of platinum group metal relative to the total mass of component (A), and is preferably 1 to 500 ppm. If the blending amount is too small, the curability will decrease, and if the blending amount is too large, the cost will increase and it will be uneconomical. The platinum group metal catalyst of component (C) may be used alone or in combination of two or more kinds.
[0032] [(D) component] Component (D) is a thermally conductive powder for imparting thermal conductivity to the silicone rubber composition of the present invention, and has an average primary particle size of 75 μm or less and a thermal conductivity of 10 to 5,000 W / m K. The silicone rubber composition of the present invention is prepared by blending the above-mentioned organopolysiloxane (A) with a specific thermally conductive powder (D).
[0033] The thermally conductive powder used in the present invention has a thermal conductivity of 10 to 5,000 W / m·K, preferably 20 to 5,000 W / m·K, and more preferably 40 to 5,000 W / m·K. If the thermal conductivity of the thermally conductive powder is less than 10 W / m·K, it is necessary to add a large amount of the thermally conductive powder to the silicone rubber composition, which is unsuitable because it causes a decrease in the elastic modulus and an increase in hardness in the cured silicone rubber.
[0034] The average primary particle size of the thermally conductive powder used in the present invention is 75 μm or less, and is usually 50 μm or less, preferably 0.1 to 30 μm, more preferably 0.5 to 20 μm, and particularly preferably 2 to 15 μm. If the average primary particle size is 0.1 μm or more, the particles are easy to manufacture, have good dispersibility in silicone polymers (for example, the alkenyl-containing organopolysiloxane of the base polymer (A)), and are easy to disperse the primary particles and to incorporate in large amounts. If the average primary particle size exceeds 75 μm, not only will the mechanical strength of the rubber cured product be impaired, but the surface will become uneven, especially when used as a developing rubber member such as a developing roll or developing belt, and problems may occur in performance such as image characteristics and toner transferability.
[0035] In the present invention, the average primary particle size can be determined as the cumulative weight average value D50 (or median size) using a particle size distribution measuring device by a laser light diffraction method or the like.
[0036] Specific examples of the thermally conductive powder include thermally conductive inorganic powders such as metallic silicon powder, alumina, aluminum, silicon carbide, silicon nitride, magnesium oxide, magnesium carbonate, zinc oxide, and aluminum nitride.
[0037] Among them, metal silicon powder is most suitable for use in the present invention. Metal silicon has good thermal conductivity and low Mohs hardness. Metal silicon has the characteristics of being easily broken down when struck and having low malleability, so that the metal powder itself does not easily aggregate even when subjected to high shear. Therefore, it is easy to pulverize into fine particles and has the characteristics of excellent dispersibility in organopolysiloxane. Therefore, when polishing an electrophotographic image forming member containing metal silicon powder, it is possible to obtain a rubber member with good polishing properties and excellent surface smoothness. It is also more preferable to use metallic silicon powder in combination with other thermally conductive powders, since this makes it possible to obtain a silicone rubber composition that has the properties of both the thermally conductive powders. Examples of thermally conductive powders having a Mohs hardness higher than that of metallic silicon powder include silicon carbide, alumina, aluminum nitride, and silicon nitride.
[0038] In addition, for the purpose of improving the thermal stability of the silicone rubber composition and the compounding ability of the thermally conductive powder, the thermally conductive powder of component (D) is preferably surface-treated with a surface treatment agent such as a silane coupling agent or a partial hydrolysate thereof, an alkylalkoxysilane or a partial hydrolysate thereof, an organic silazanes, a titanate coupling agent, an organopolysiloxane oil, or an organopolysiloxane containing a hydrolyzable functional group.
[0039] The amount of the thermally conductive powder of component (D) is 10 to 1,000 parts by mass, preferably 40 to 600 parts by mass, and more preferably 50 to 400 parts by mass, per 100 parts by mass of component (A). If the amount is less than 10 parts by mass, the desired high thermal conductivity cannot be obtained, and if the amount exceeds 1,000 parts by mass, the rubber elasticity is reduced and physical properties such as rubber strength are also significantly reduced.
[0040] Furthermore, since the highly thermally conductive silicone rubber members obtained from the silicone rubber composition of the present invention are used in image forming devices that utilize electrophotography, and therefore good rubber elasticity and good compression set are particularly required, it is desirable to adjust the blending amount of the thermally conductive powder so as to optimize the above-mentioned properties.
[0041] [(E) component] Component (E) functions as a protective agent for the platinum catalyst of component (C) and is different from component (A). Component (E) is one or more types selected from the following alkenyl group-containing polysiloxanes: (E-1) Alkenyl-containing cyclic organopolysiloxane having one or more alkenyl groups on all silicon atoms (E-2) The content of alkenyl groups bonded to silicon atoms is 1.1 x 10 -3 ~1.0×10 -1 mol / g of alkenyl-containing linear organopolysiloxane The component (E) is characterized by its good storage stability and does not act as a catalyst poison when added to the same composition. Reaction inhibitors generally used in addition-curing organopolysiloxane compositions are intended to suppress the catalytic activity of the addition reaction catalyst, thereby preventing the hydrosilylation reaction from proceeding, thereby improving storage stability. In contrast, the protective agent, which is the component (E) of the present invention, is intended to protect the (C) addition reaction catalyst from the cure retardation action of the component (D) and to prevent the cure characteristics of the silicone rubber composition of the present invention from slowing down over time. Specifically, it is presumed that the (E) component prevents the (D) component from absorbing the (C) component. In addition, this cure retardation suppression effect was discovered for the first time by the present inventors. Since the metal silicon powder of the (D) component has a low Mohs hardness, when other thermally conductive powders are used in combination, the thermally conductive powders are often high in Mohs hardness. When a thermally conductive powder with a higher Mohs hardness than the metal silicon powder is used in combination with metal silicon, the metal silicon surface is scraped and broken. Therefore, a new metal silicon surface appears, which may easily absorb the addition cure catalyst. Even in such a case, the protective agent, which is the component (E) of the present invention, protects the (C) addition reaction catalyst from the cure retardation action of the component (D). The alkenyl-containing cyclic organopolysiloxane of the component (E-1) is a cyclic organopolysiloxane having one or more alkenyl groups on all silicon atoms, and is particularly preferably represented by the following general formula (1). [ka] (In the formula, R 1 is a methyl group or a vinyl group, and p is 3 to 30. p is 3 to 30, preferably 4 to 20, and more preferably 4 to 10. The structure within the above range allows the components (C), (D), and (E) to be mixed together, and even in a state in which the component (D) adversely affects the component (C), the component (C) is not inactivated and storage stability over time can be obtained. Specific examples include the following.
[0042] [ka]
[0043] The alkenyl-containing linear organopolysiloxane of component (E-2) has a content of alkenyl groups bonded to silicon atoms of 1.1×10 relative to the total number of monovalent hydrocarbon groups bonded to silicon atoms. -3 ~1.0×10 -1 mol / g, and is represented, for example, by the following average composition formula (a), with the structure represented by the following general formula (2) being particularly preferred. R c Vi d SiO (4-c-d) / 2 (a) (In the formula, R is independently a monovalent hydrocarbon group having 1 to 10 carbon atoms, preferably 1 to 8 carbon atoms, not containing an aromatic group, and Vi is a vinyl group. In addition, c is a positive number that satisfies 0.7 to 2.1, d is a positive number that satisfies 0.001 to 1.0, and c+d is a positive number that satisfies 0.8 to 3.0.)
[0044] [ka] (In the formula, R is independently a monovalent hydrocarbon group having 1 to 10 carbon atoms, q is 0 or more, r is 2 or more, and q+r is 2 to 200.)
[0045] Examples of monovalent hydrocarbon groups having 1 to 10 carbon atoms represented by R include alkyl groups such as methyl, ethyl, propyl, isopropyl, butyl, isobutyl, tert-butyl, pentyl, neopentyl, hexyl, cyclohexyl, octyl, nonyl, and decyl, and alkenyl groups such as vinyl, allyl, propenyl, isopropenyl, butenyl, hexenyl, cyclohexenyl, and octenyl. Groups in which some or all of the hydrogen atoms of these groups have been substituted with halogen atoms such as fluorine or chlorine, such as chloromethyl, chloropropyl, and trifluoropropyl, may also be used.
[0046] In the case of the above general formula (2), q is 0 or more, r is 2 or more, and q+r is 2 to 200, preferably q is 0 or more, r is 4 or more, and q+r is 4 to 100, and more preferably q is 0 or more, r is 4 or more, and q+r is 4 to 50. The content of alkenyl groups bonded to silicon atoms is 1.1×10 relative to the total number of monovalent hydrocarbon groups bonded to silicon atoms. -3 ~1.0×10 -1 mol / g, 2.0×10 -3 ~1.0×10 -1 It is preferably expressed in mol / g. The structure within the above range allows the components (C), (D), and (E) to be mixed together, and even in a state in which the component (D) adversely affects the component (C), the component (C) is not inactivated and storage stability over time can be obtained. Specific examples include the following.
[0047] [ka]
[0048] The amount of the (E) component is 0.1 to 500 mol / mol, preferably 0.1 to 300 mol / mol, and more preferably 0.1 to 200 mol / mol, of the platinum group metal catalyst (C) (component (E) / platinum group metal atom (Pt, Pd, Rh, etc.). If the amount is 0.1 to 500 mol / mol, the (C) component is not deactivated and storage stability over time can be obtained even when the (C) component, the (D) component, and the (E) component are mixed and the (D) component has an adverse effect on the (C) component. If the amount is less than 1 mol / mol, the (C) component is deactivated and storage stability over time cannot be obtained. If the amount is more than 500 mol / mol, the silicone rubber cured product becomes brittle. The (E) component may be used alone or in combination of two or more types.
[0049] [Reinforcing silica powder] The addition of inorganic fillers other than the above-mentioned components (A) to (E) to the silicone rubber composition of the present invention is optional, and a reinforcing silica fine powder can be added.
[0050] The reinforcing silica fine powder has a specific surface area of 10 m2 as measured by the BET adsorption method in order to obtain a silicone rubber composition with excellent mechanical strength. 2 / g or more, especially 50-400m 2 / g. Examples of reinforcing silica fine powder include fumed silica (dry silica) and precipitated silica (wet silica), and among these, fumed silica (dry silica) is preferred.
[0051] Examples of commercially available reinforcing silica fine powders that can be used include Aerosil 130, 200, 300 (trade names of Nippon Aerosil Co., Ltd.), Cab-O-sil MS-5, MS-7, HS-5, HS-7 (trade names of Cabot Corporation), Santocel FRC, CS (trade names of Monsanto Co., Ltd.), and Nipsil VN-3 (trade name of Nippon Silica Industry Co., Ltd.). The surfaces of these silica powders may be hydrophobized with organopolysiloxane, organopolysilazane, chlorosilane, alkoxysilane, etc. These silica powders may be used alone or in combination of two or more kinds.
[0052] From the viewpoints of improving compression set and further suppressing the increase in volume resistivity over time, it is desirable to add a small amount of the reinforcing silica fine powder to the silicone rubber composition.
[0053] In order to obtain better volume resistivity and compression set while blending the reinforcing silica fine powder, the blending amount is preferably 0 to 5 parts by mass, and more preferably 0 to 3 parts by mass, per 100 parts by mass of the organopolysiloxane of component (A) in the silicone rubber composition. The lower limit of the blending amount can be 0.1 parts by mass or more.
[0054] [Other inorganic fillers, etc.] Examples of inorganic fillers other than the reinforcing silica fine powder include diatomaceous earth, perlite, mica, calcium carbonate, glass flakes, and hollow fillers.
[0055] These inorganic fillers may be surface-treated with a silane coupling agent or a partial hydrolysate thereof, an alkylalkoxysilane or a partial hydrolysate thereof, an organic silazanes, a titanate coupling agent, an organopolysiloxane oil, an organopolysiloxane containing a hydrolyzable functional group, etc. Such treatment may be performed by previously treating the inorganic filler itself, or may be performed when mixing with the oil.
[0056] The amount blended is preferably about 0 to 400 parts by mass per 100 parts by mass of the organopolysiloxane of the component (A) in the silicone rubber composition.
[0057] Furthermore, if necessary, it is also possible to optionally blend in a hydrosilylation reaction inhibitor such as a nitrogen-containing compound such as an amine compound, an acetylene compound such as an acetylene alcohol having an ethynyl group, an organic phosphorus compound such as a phosphine, or an organic sulfur compound such as a sulfide, various additives, a flame retardant, a heat resistance agent, or the like.
[0058] [Preparation of addition-curable liquid silicone rubber composition and molding thereof] The addition-curable liquid silicone rubber composition of the present invention can be prepared by uniformly mixing the above components (A) to (E), as well as other components (reinforcing silica fine powder and other inorganic fillers) as necessary, using a conventional mixer / stirrer or kneader such as a kneader or planetary mixer.
[0059] The silicone rubber composition of the present invention can be molded by cast molding, injection molding, coating, etc., and the curing conditions preferably include press curing for 10 seconds to 1 hour at a temperature of 100 to 300° C. In order to reduce low molecular weight siloxane components that cause a decrease in compression set, a post cure (secondary cure) may be performed in an oven at 120 to 250° C. for about 30 minutes to 70 hours after molding.
[0060] <Electrophotographic image forming member> The present invention also provides an electrophotographic image forming member having an elastic layer made of a cured product of the above-mentioned addition-curable liquid silicone rubber composition. Such an electrophotographic image forming member is preferably a member selected from a fixing roll and a fixing belt.
[0061] For example, it may be used as a single-layer roll in which the outer periphery of a core metal is coated with a silicone rubber layer which is a cured product of the silicone rubber composition of the present invention, or as a single-layer belt in which the front and back surfaces of a substrate made of a heat-resistant resin or metal are coated with a silicone rubber layer which is a cured product of the silicone rubber composition of the present invention, or as a roll or belt in which a resin such as a polyimide resin, a urethane resin, or a fluorine-based resin is further coated on the silicone rubber layer. In this case, the silicone rubber layer may be a single layer coating on the surface (outer periphery) or a multi-layer coating of two or more layers. Among them, those in which a urethane resin, a fluorine-based resin, or the like is coated on the outermost surface of a roll or belt are preferred from the viewpoint of durability such as abrasion resistance.
[0062] Here, the material of the core metal or the substrate is preferably selected from iron, stainless steel, aluminum, polyamide / polyimide resin, and PEEK (polyether ether ketone).
[0063] As the fluorine-based resin, a fluorine-based resin coating material or a fluorine-based resin tube can be used. Examples of the fluorine-based resin coating material include polytetrafluoroethylene resin (PTFE) latex and Dai-el latex (fluorine-based latex, manufactured by Daikin Industries, Ltd.). As the fluorine-based resin tube, a commercially available product can be used, such as polytetrafluoroethylene resin (PTFE), tetrafluoroethylene-perfluoroalkyl vinyl ether copolymer resin (PFA), fluorinated ethylene-polypropylene copolymer resin (FEP), polyvinylidene fluoride resin (PVDF), polyvinyl fluoride resin, etc., and among these, PFA and PTFE latex are particularly preferred. EXAMPLES
[0064] The present invention will be described in detail below with reference to examples and comparative examples, but the present invention is not limited to the following examples. Note that the viscosity described below is a value measured at 25°C using a rotational viscometer as described in JIS K 7117-1:1999.
[0065] Example 1 Both ends of the molecular chain are capped with vinyldimethylsiloxy groups, and the amount of alkenyl groups is 1.5×10 -4 83 parts by mass of dimethylpolysiloxane (A1) with a viscosity of 500 mPa s and a molecular chain end capped with trimethylsiloxy groups and an alkenyl group content of 1.0 × 10 -4 20 parts by mass of dimethylpolysiloxane (A2) having a vinyl group in the side chain and a viscosity of 15,000 mPa s, 0.16 parts by mass of 1-ethynylcyclohexanol, 0.3 parts by mass of dimethylpolysiloxane solution (C) containing chloroplatinic acid / 1,3-divinyltetramethyldisiloxane complex with a platinum atom content of 1% by mass, and a BET specific surface area of 110 m 2 The composition consisted of 1 part by mass of hydrophobically treated fumed silica (R-972 manufactured by Nippon Aerosil Co., Ltd.) having a molecular weight of 1.0 to 1.0 kg / g, 200 parts by mass of pulverized metal silicon powder (D1) (average primary particle size 5 μm, thermal conductivity 168 W / m K), 60 parts by mass of pulverized silicon carbide powder (D2) (average primary particle size 9 μm, thermal conductivity 270 W / m K), 0.01 parts by mass (2 moles per Pt atom) of 1,3,5,7-tetravinyltetramethylcyclotetrasiloxane (E1), and a dimethylsiloxane-methylhydrogensiloxane copolymer (B) having a molecular weight of 1.0 to 1.0 kg / g and a molecular weight of 1.0 to 1.0 kg / g, and a molecular weight of 1.0 to 1.0 kg / g. -3 The components (4.02 parts by mass, 1.0 mol / g) were blended in this order and mixed for 30 minutes with a planetary mixer at room temperature (25°C) to prepare composition A. Next, the prepared composition A was press-cured at 120°C for 10 minutes to form a silicone rubber sheet, which was then post-cured at 200°C for 4 hours, and the hardness was measured according to JIS K 6249:2003. The results are shown in Table 2.
[0066] Next, in order to confirm the storage stability, Compositions A1 and A2 were prepared as follows. Compositions A1 and A2 were prepared by mixing the catalyst and crosslinking agent separately, the components (E) and (C) in the same amounts in a mass ratio of 1:1 to form Composition A.
[0067] [Preparation of Composition A1] 44 parts by mass of dimethylpolysiloxane (A1) in which both molecular chain terminals are blocked with vinyldimethylsiloxy groups, 10 parts by mass of dimethylpolysiloxane (A2) in which both molecular chain terminals are blocked with trimethylsiloxy groups and which has vinyl groups on the side chains, 0.3 parts by mass of dimethylpolysiloxane solution (C) containing 1% by mass of chloroplatinic acid / 1,3-divinyltetramethyldisiloxane complex as platinum atom content, 100 parts by mass of pulverized metallic silicon powder (D1), 30 parts by mass of pulverized silicon carbide powder (D2), 0.01 parts by mass of 1,3,5,7-tetravinyltetramethylcyclotetrasiloxane (E1) (2 moles per mole of Pt atom, BET specific surface area of 110 m 2 0.5 parts by mass of hydrophobized fumed silica (R-972, manufactured by Nippon Aerosil Co., Ltd.) having a molecular weight of 1.0 to 1.0 g / g was mixed with a planetary mixer at room temperature (25° C.) for 30 minutes to prepare composition A1.
[0068] [Preparation of Composition A2] Next, 39 parts by mass of dimethylpolysiloxane (A1) whose molecular chain ends are blocked with vinyldimethylsiloxy groups, 10 parts by mass of dimethylpolysiloxane (A2) whose molecular chain ends are blocked with trimethylsiloxy groups and have vinyl groups on the side chains, 4.02 parts by mass of dimethylsiloxane-methylhydrogensiloxane copolymer (B) whose molecular chain ends are blocked with trimethylsiloxy groups and have silicon-bonded hydrogen atoms on the side chains, 100 parts by mass of pulverized metallic silicon powder (D1), 30 parts by mass of pulverized silicon carbide powder (D2), 0.16 parts by mass of 1-ethynylcyclohexanol, and a copolymer having a BET specific surface area of 110 m 2 0.5 parts by mass of hydrophobized fumed silica (R-972, manufactured by Nippon Aerosil Co., Ltd.) having a molecular weight of 1.0 to 1.0 g was mixed with 0.5 parts by mass of hydrophobized fumed silica (R-972, manufactured by Nippon Aerosil Co., Ltd.) at room temperature (25° C.) for 30 minutes to prepare composition A2.
[0069] [Evaluation of storage stability] Next, composition A1 and composition A2 were each sealed and stored at 25°C for 12 months or at 80°C for 3 days. Composition A1 and composition A2 were mixed at a mass ratio of 1:1 at the initial preparation stage (3 days at 25°C) or after storage to form composition A, and then the curability T10 and T90 at 130°C were measured using a rheometer MDR2000 (manufactured by Alpha Technologies), and the results are shown in Table 1. Curability T10 and T90 refer to the time T10 to reach 10% of the maximum torque value measured by the rheometer, and the time T90 to reach 90% of the maximum torque value, when the maximum torque value measured by the rheometer is taken as 100.
[0070] Example 2 Composition B was prepared according to the same recipe as in Example 1, except that the 4.02 parts by mass of dimethylsiloxane-methylhydrogensiloxane copolymer (B) was replaced by 4.3 parts by mass, and the 0.01 parts by mass of 1,3,5,7-tetravinyltetramethylcyclotetrasiloxane (E1) was replaced by 0.1 parts by mass (19 moles relative to Pt atoms), and evaluation was performed in the same manner as in Example 1. The storage stability was confirmed only under the condition of 80°C for 3 days, and the results are shown in Table 2.
[0071] Example 3 Composition C was prepared using the same recipe as in Example 1, except that the 4.02 parts by mass of dimethylsiloxane-methylhydrogensiloxane copolymer (B) was replaced by 4.14 parts by mass, and the 0.01 parts by mass of 1,3,5,7-tetravinyltetramethylcyclotetrasiloxane (E1) was replaced by 0.05 parts by mass (9 moles relative to Pt atoms), and evaluation was performed in the same manner as in Example 1. The storage stability was confirmed only under the condition of 80°C for 3 days, and the results are shown in Table 2.
[0072] Example 4 Composition D was prepared using the same recipe as in Example 1, except that the 4.02 parts by mass of dimethylsiloxane-methylhydrogensiloxane copolymer (B) was replaced by 3.99 parts by mass, and the 0.01 parts by mass of 1,3,5,7-tetravinyltetramethylcyclotetrasiloxane (E1) was replaced by 0.005 parts by mass (1 mole per Pt atom), and evaluation was performed in the same manner as in Example 1. The storage stability was confirmed only under the condition of 80°C for 3 days, and the results are shown in Table 2.
[0073] Example 5 In Example 1, 4.02 parts by mass of dimethylsiloxane-methylhydrogensiloxane copolymer (B) was mixed with 4.14 parts by mass of 1,3,5,7-tetravinyltetramethylcyclotetrasiloxane (E1) and 0.01 parts by mass of a compound represented by the following general formula (I): [ka] Composition E was prepared using the same recipe except that 0.3 parts by mass (13 moles per Pt atom) of an alkenyl-containing linear organopolysiloxane (E2) represented by the following formula was substituted, and the composition was evaluated in the same manner as in Example 1. The storage stability was confirmed only under the condition of 80°C for 3 days, and the results are shown in Table 2.
[0074] Example 6 In Example 1, 4.02 parts by mass of dimethylsiloxane-methylhydrogensiloxane copolymer (B) was mixed with 3.99 parts by mass of 1,3,5,7-tetravinyltetramethylcyclotetrasiloxane (E1) and 0.01 parts by mass of an alkenyl group represented by the above general formula (I). Composition F was prepared using the same recipe except that 0.03 parts by mass (1 mole per Pt atom) of the chain organopolysiloxane (E2) was used instead, and evaluated in the same manner as in Example 1. The storage stability was confirmed only under the condition of 80°C for 3 days, and the results are shown in Table 2.
[0075] Example 7 In Example 1, 83 parts by mass of dimethylpolysiloxane (A1) in which both molecular chain terminals are blocked with vinyldimethylsiloxy groups was replaced by 62 parts by mass, 20 parts by mass of dimethylpolysiloxane (A2) in which both molecular chain terminals are blocked with trimethylsiloxy groups and which has vinyl groups on the side chains was replaced by 38 parts by mass, 0.16 parts by mass of 1-ethynylcyclohexanol was replaced by 0.17 parts by mass, and a BET specific surface area of 110 m was replaced by 0.25 parts by mass. 2 Composition G was prepared according to the same recipe as in Example 1, except that 1 part by mass of hydrophobized fumed silica (R-972 manufactured by Nippon Aerosil Co., Ltd.) having a molecular weight of 1.001 to 1.001 g was not added, pulverized metal silicon powder (D1) (average primary particle size 5 μm) was not added instead of 200 parts by mass, pulverized silicon carbide powder (D2) (average primary particle size 9 μm) was not added instead of 105 parts by mass, pulverized silicon carbide powder (D2) (average primary particle size 9 μm) was not added instead of 60 parts by mass, 1,3,5,7-tetravinyltetramethylcyclotetrasiloxane (E1) was replaced by 0.005 parts by mass (1 mole per Pt atom), and dimethylsiloxane-methylhydrogensiloxane copolymer (B) having both molecular chain ends blocked with trimethylsiloxy groups and silicon atom-bonded hydrogen atoms in the side chain was replaced by 4.02 parts by mass instead of 3.25 parts by mass, and evaluation was performed in the same manner as in Example 1. The storage stability was confirmed only under the condition of 80°C for 3 days, and the results are shown in Table 2.
[0076] Example 8 In Example 1, 83 parts by mass of dimethylpolysiloxane (A1) in which both molecular chain terminals are blocked with vinyldimethylsiloxy groups was replaced by 62 parts by mass, 20 parts by mass of dimethylpolysiloxane (A2) in which both molecular chain terminals are blocked with trimethylsiloxy groups and which has vinyl groups on the side chains was replaced by 38 parts by mass, 0.16 parts by mass of 1-ethynylcyclohexanol was replaced by 0.17 parts by mass, and a BET specific surface area of 110 m was replaced by 0.25 parts by mass. 2 / g) of 1 part by mass of hydrophobized fumed silica (R-972 manufactured by Nippon Aerosil Co., Ltd.), 200 parts by mass of pulverized metal silicon powder (D1) (average primary particle diameter 5 μm) is not added to 105 parts by mass, and 60 parts by mass of pulverized silicon carbide powder (D2) (average primary particle diameter 9 μm) is not added to 105 parts by mass, and 0.01 parts by mass of 1,3,5,7-tetravinyltetramethylcyclotetrasiloxane (E1) is not added to the alkenyl group-containing chain-linked siloxane represented by the above general formula (I). Composition H was prepared using the same formulation as in Example 1, except that 0.03 parts by mass (1 mole per Pt atom) of organopolysiloxane (E2) and 4.02 parts by mass of dimethylsiloxane-methylhydrogensiloxane copolymer (B) capped at both molecular chain terminals with trimethylsiloxy groups and having silicon-bonded hydrogen atoms in the side chains were replaced by 3.25 parts by mass, and evaluations were carried out in the same manner as in Example 1. Storage stability was confirmed only under the condition of 80°C for 3 days, and the results are shown in Table 2.
[0077] Comparative Example 1 83 parts by mass of dimethylpolysiloxane (A1) in which both molecular chain terminals are blocked with vinyldimethylsiloxy groups, 20 parts by mass of dimethylpolysiloxane (A2) in which both molecular chain terminals are blocked with trimethylsiloxy groups and which has vinyl groups on the side chains, 0.16 parts by mass of 1-ethynylcyclohexanol, 0.3 parts by mass of a dimethylpolysiloxane solution (C) containing chloroplatinic acid / 1,3-divinyltetramethyldisiloxane complex with a platinum atom content of 1% by mass, and a BET specific surface area of 110 m 2 Composition I was prepared by mixing 1 part by mass of hydrophobically treated fumed silica (R-972, manufactured by Nippon Aerosil Co., Ltd.) having a molecular weight of 1.001 mg / g, 200 parts by mass of pulverized silicon metal powder (D1), 60 parts by mass of pulverized silicon carbide powder (D2), and 3.99 parts by mass of a dimethylsiloxane-methylhydrogensiloxane copolymer having silicon-bonded hydrogen atoms in its side chains (B) in a planetary mixer at room temperature for 30 minutes, and evaluations were carried out in the same manner as in Example 1. The results are shown in Table 2.
[0078] Next, in order to confirm the storage stability, compositions I1 and I2 were prepared as follows. The compositions I1 and I2 were prepared by mixing the catalyst and crosslinking agent separately in a mass ratio of 1:1 to form the composition I.
[0079] [Preparation of Composition I1] 44 parts by mass of dimethylpolysiloxane (A1) in which both molecular chain terminals are blocked with vinyldimethylsiloxy groups, 10 parts by mass of dimethylpolysiloxane (A2) in which both molecular chain terminals are blocked with trimethylsiloxy groups and which has vinyl groups on the side chains, 0.3 parts by mass of dimethylpolysiloxane solution (C) containing chloroplatinic acid / 1,3-divinyltetramethyldisiloxane complex with a platinum atom content of 1% by mass, 100 parts by mass of pulverized metallic silicon powder (D1), 30 parts by mass of pulverized silicon carbide powder (D2), and a tertiary siloxane having a BET specific surface area of 110 m 2 0.5 parts by mass of hydrophobized fumed silica (R-972, manufactured by Nippon Aerosil Co., Ltd.) having a molecular weight of 1.0 to 1.0 g was added in this order, and mixed at room temperature for 30 minutes with a planetary mixer to prepare composition I1.
[0080] [Preparation of Composition I2] Next, 39 parts by mass of dimethylpolysiloxane (A1) whose molecular chain ends are blocked with vinyldimethylsiloxy groups, 10 parts by mass of dimethylpolysiloxane (A2) whose molecular chain ends are blocked with trimethylsiloxy groups and have vinyl groups on the side chains, 3.99 parts by mass of dimethylsiloxane-methylhydrogensiloxane copolymer (B) whose molecular chain ends are blocked with trimethylsiloxy groups and have silicon-bonded hydrogen atoms on the side chains, 100 parts by mass of pulverized metallic silicon powder (D1), 30 parts by mass of pulverized silicon carbide powder (D2), 0.16 parts by mass of 1-ethynylcyclohexanol, and a copolymer having a BET specific surface area of 110 m 2 Composition I2 was prepared by mixing 0.5 parts by mass of hydrophobized fumed silica (R-972, manufactured by Nippon Aerosil Co., Ltd.) having a molecular weight of 1.0 to 1.0 g with a planetary mixer at room temperature for 30 minutes.
[0081] [Evaluation of storage stability] Next, composition I1 and composition I2 were each sealed and stored at 80° C. for 3 days. Composition I1 and composition I2 were mixed in a 1:1 ratio at the initial stage of preparation (3 days at 25° C.) or after storage to prepare composition I, and the curability T10 and T90 at 130° C. were measured using a rheometer MDR2000 (manufactured by Alpha Technologies). The results are shown in Table 1.
[0082] Comparative Example 2 Composition J was prepared according to the same recipe as in Comparative Example 1, except that 0.16 parts by mass of 1-ethynylcyclohexanol was replaced by 0.32 parts by mass, and 0.3 parts by mass of the dimethylpolysiloxane solution (C) containing chloroplatinic acid / 1,3-divinyltetramethyldisiloxane complex at 1% by mass in terms of platinum atom content was replaced by 0.75 parts by mass, and evaluation was performed in the same manner as in Example 1. Regarding storage stability, the results of checking only the condition of 80°C for 3 days are shown in Table 2.
[0083] Comparative Example 3 In Comparative Example 1, the compound represented by the following general formula (II) [ka] Composition K was prepared in the same manner as in Example 1, except that 8 parts by mass of an alkoxy group-containing siloxane compound represented by the following formula was added, and evaluated in the same manner as in Example 1. The storage stability was confirmed only under the condition of 80°C for 3 days, and the results are shown in Table 2.
[0084] Comparative Example 4 Composition L was prepared using the same recipe as in Comparative Example 1, except that 60 parts by mass of pulverized silicon carbide powder (D2) was replaced with 75 parts by mass of pulverized alumina (D3) (average primary particle size 3 μm, thermal conductivity 36 W / m K), and evaluated in the same manner as in Example 1. The storage stability was confirmed only under the condition of 80°C for 3 days, and the results are shown in Table 2.
[0085] Comparative Example 5 Composition M was prepared using the same recipe as in Comparative Example 1, except that 60 parts by mass of the pulverized silicon carbide powder (D2) was replaced with 75 parts by mass of spherical alumina (D4) (average primary particle size 3 μm, thermal conductivity 36 W / m K), and evaluated in the same manner as in Example 1. The storage stability was confirmed only under the condition of 80°C for 3 days, and the results are shown in Table 2.
[0086] Comparative Example 6 In Comparative Example 1, 83 parts by mass of dimethylpolysiloxane (A1) in which both molecular chain terminals are blocked with vinyldimethylsiloxy groups was replaced by 62 parts by mass, 20 parts by mass of dimethylpolysiloxane (A2) in which both molecular chain terminals are blocked with trimethylsiloxy groups and which has vinyl groups on the side chains was replaced by 38 parts by mass, 0.16 parts by mass of 1-ethynylcyclohexanol was replaced by 0.17 parts by mass, and a BET specific surface area of 110 m was replaced by 0.25 parts by mass. 2 Composition N was prepared according to the same recipe as in Example 1, except that 1 part by mass of hydrophobically treated fumed silica (R-972, manufactured by Nippon Aerosil Co., Ltd.) having a molecular weight of 1000 to 1050 g / g was not added, the pulverized silicon metal powder (D1) was replaced by 200 parts by mass, and the pulverized silicon carbide powder (D2) was replaced by 60 parts by mass, and the dimethylsiloxane-methylhydrogensiloxane copolymer (B) having silicon-bonded hydrogen atoms in its side chains was replaced by 3.25 parts by mass, and evaluation was performed in the same manner as in Example 1. Storage stability was confirmed only under conditions of 80°C for 3 days, and the results are shown in Table 2.
[0087] [Table 1]
[0088] [Table 2]
[0089] In Examples 1 to 8, a sufficient amount of component (E) was included, preventing the adverse effect of component (D) on component (C), and the storage stability was good, and the curing property did not deteriorate after storage while having good thermal conductivity. In contrast, in Comparative Examples 1 to 6, which did not include component (E), a noticeable delay in curing property occurred after storage.
Claims
1. (A) A compound having two or more alkenyl groups bonded to silicon atoms in one molecule, and the content of the alkenyl groups bonded to silicon atoms is 1.0×10 relative to the total number of monovalent hydrocarbon groups bonded to silicon atoms. -7 ~1.0 x 10 -3 mol / g liquid organopolysiloxane: 100 parts by mass, (B) an organohydrogenpolysiloxane containing two or more hydrosilyl groups per molecule: the number of hydrosilyl groups contained in component (B) is 0.4 to 10 per alkenyl group bonded to a silicon atom contained in component (A); (C) a platinum group metal catalyst as an addition reaction catalyst: an amount equivalent to 0.5 to 1,000 ppm in terms of platinum group metal based on the total mass of component (A); (D) a thermally conductive powder having an average primary particle size of 75 μm or less and a thermal conductivity of 10 W / m·K or more: 10 to 1,000 parts by mass, and (E) The content of alkenyl groups bonded to silicon atoms is 1.1 x 10 based on the total number of monovalent hydrocarbon groups bonded to silicon atoms. -3 ~1.0 x 10 -1 mol / g, and the organopolysiloxane has the following general formula (2): 【Chemistry 1】 (In the formula, R is independently a monovalent hydrocarbon group having 1 to 10 carbon atoms, q is 0 or more, r is 2 or more, and q+r is 2 to 200.) an alkenyl-containing linear organopolysiloxane represented by the formula:
2. 2. The addition-curable liquid silicone rubber composition according to claim 1, wherein component (D) is metallic silicon powder.
3. 2. The addition-curing liquid silicone rubber composition according to claim 1, wherein component (D) is a metallic silicon powder or a thermally conductive powder having a Mohs hardness higher than that of the metallic silicon powder.
4. 4. An electrophotographic image forming member having an elastic layer made of a cured product of the addition-curable liquid silicone rubber composition according to claim 1.
5. 5. The electrophotographic imaging member of claim 4, wherein said electrophotographic imaging member is a member selected from a fuser roll and a fuser belt.
Citation Information
Patent Citations
Silicone rubber composition for high-heat-conductivity heat fixing roll or fixing belt, and heat fixing roll or fixing belt
JP2007171946A
Highly thermally-conductive silicone rubber composition, heat fixing roll and fixing belt
JP2009263405A
Method for producing pulverized metal silicon powder
JP2013216576A
Two-liquid addition curing type silicone rubber composition
JP2021187877A
Silicone rubber composition for thermally conductive silicone-rubber development member, and thermally conductive silicone-rubber development member
WO2014203669A1